Vaccination Against Infectious Bursal Disease Virus (IBDV) in Broiler Birds in Mozambique: Are We Doing Enough? - Muchanga, E.F.; Frechaut, E.R.C.; Taunde, P.; Nhambirre, O.; Junior, A.M.; Bila , C.G. (International Journal of Poultry Science, 2015)
Although regularly vaccinated, IBD outbreaks are frequently reported in broiler birds in Mozambique, which may suggest poor immunization. To test this hypothesis, this study aimed to detect maternally derived antibodies titers in commercial unvaccinated 1-d-old chicks and to evaluate humoral immune status of vaccinated adult chicken broilers against IBD virus from Matola and Maputo regions. Serum samples were collected from unvaccinated broiler day-old chicks (n = 250) and vaccinated adult broiler chicken (n = 300). A commercial ELISA kit was used to determine the titer of mAb. Our results revealed that one day old chicks presented high protective antibodies titers and good and low coefficient of variation (CV), which indicated optimal maternal immunity transfer. Only 28% of adult broiler serum samples had protective antibody titers and more than 1/3 were seronegative. In addition, as little as 27% of analyzed flocks were considered protected against IBD virus. Taken together, this data suggest that, unlike what has been found in 1-d-old chicks, the evaluated adult broiler poultry population were susceptible to IBDV, which may explain the frequently outbreaks reported in those regions.